annotated historical account of canine parvovirus - Carmichael, L.E (Journal of veterinary medicine. Series B, 2005)
A brief annotated history of canine parvovirus-type 2 (CPV-2) and its variants is summarized with emphasis on the most significant contributions of individuals involved in the initial recognition of CPV-2 and subsequent discoveries that have advanced our knowledge of the nature and evolution of this novel canine virus. Time has obscured the observations of many veterinary clinicians and researchers throughout the world who sensed the presence of a new disease when CPV-2 first made its appearance in 1978 and then, within 1-2 years, spread worldwide. Since 1979, nearly 600 articles, papers, numerous text chapters and monographs have been published on the subject of CPV-2. The early history is well known by veterinary infectious diseases specialists and noteworthy publications are recorded on the National Library of Medicine (USA) website, PubMed and in review articles. Because of the great number of publications, it is not practicable to cite them individually; however, reference is made to certain individuals, reviews and selected papers that I consider particularly relevant to the history of progress in the understanding of CPV-2 and the disease it causes. The clinical disease caused by CPV-2 and its variants, the immune response to infection or vaccines, host range and the development of practical diagnostic assays are noted in historical context. The basic biological properties and the physical, molecular and antigenic structure of CPV-2 and its variants are also discussed briefly. Finally, key players who have contributed to the antigenic and DNA sequence (evolutionary) relationships between CPV-2 and the other autonomous parvoviruses of carnivores are noted and hypotheses regarding the origin and evolution of CPV-2 and its variants are mentioned.